Struktural pada Puisi Razan, Untuk Palestina Dari Saudaramu Indonesia, Dan Apakah Sampai Padamu Berita Tentang Mahananzi? Karya Helvy Tiana Rosa - Zebua Trizga Ramadhona; Heru Prasetyo (Jurusan Pendidikan Bahasa dan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Lampung, 2025)
The poems by Helvy Tiana Rosa are a representation that has the characteristics of modern poetry that is full of emotional, symbolic, and struggle content. This study aims to describe the form of expression of inner feelings in the poems by Helvy Tiana Rosa, especially through an analysis of the poems